A dual role of dams in fragmentation and support of fish diversity across the Godavari River basin in India. Issue 6 (4th February 2014) - Khedkar, Gulab Dattarao; Lutzky, Sigal; Rathod, Sandeep; Kalyankar, Amol; David, Lior
ABSTRACT Freshwater systems are among the habitats most sensitive to environmental changes and human interference. The increasing needs in India for supplies of both fresh water and fish as a food source under the pressure of a rapidly growing population mandate identification of ways to conserve natural resources while meeting these human needs. Dams provide a partial solution for both water and food fish supplies, especially in monsoonal areas, although disruption of natural fish habitats may offset these benefits. To examine this phenomenon, the Godavari River basin in India was sampled at 32 sites, and the effects dams might have on fish species assemblages and distribution at these sites were analysed. Although the river basin was rich in species, their representation and distribution was fragmented. The surveyed fish fauna included 114 species that were classified into 12 orders. Cyprinids dominated the fauna. Few introduced and cultured species were widely distributed in the river. Some native species were barely captured, suggesting they might be at risk of loss. The presence of the Godavari dams, as has been the case elsewhere, does appear to have disturbed the species distribution. However, here, the dams also appear to have positive effects. Some dam reservoirs supported the highest levels of species diversity, and as low as five dam sites contained over 95% of all species found. The dam reservoirs may therefore represent preferred sites for conservation, and the proper management of such reservoirs may be critical to balancing human needs with sustainable conservation of fish biodiversity. Copyright © 2014 John Wiley & Sons, Ltd.